Sweet nothings : confessions of a candy lover - Perry, Sarah, 1981- (Mariner Books, 2025)
A taxonomy of sweetness, a rhapsody of artificial flavors, and a multi-faceted theory of pleasure, Sweet Nothings is made up of one hundred illustrated micro essays organized by candy color, from the red of Pop Rocks to the purple Jelly Bonbon in the Whitman's Sampler. Each entry is a meditation on taste and texture, a memory unlocked. Everyone's favorites--and least favorites--are carefully considered, including Snickers and Trader Joe's Peanut Butter Cups, as well as the beloved Good n' Plenty and Werther's Originals.